A Note on the Estimation of the Gini Index. (August 2014) - Djolov, George
This article provides a statistical decision-making framework for the Gini index through the introduction of practically usable confidence intervals for this index. The resultant intervals enable hypothesis testing with the Gini index as well as providing a mechanism for studying the reliability of its estimates. The article presents these confidence intervals and demonstrates their prospective uses with an illustrative example to officially published estimates for the index from 24 countries. JEL Classification: C02, C13